What interpretations for 'smart specialization strategies' in European urban regions? Lessons from Boston. - Monardo, Bruno (Springer, 2018)
This paper aims to highlight the crucial challenges faced by the regions of the European Union (EU) when applying the EU's 'Research and Innovation Strategies for Smart Specialisation' (RIS3) policy to implement its 'Cohesion Policy' and 'Europe 2020' agendas. The author maintains that policymakers, planners, entrepreneurs, local communities and the other stakeholders involved in the future of urban regions should adopt a fresh view of the current innovation strategies at the forefront of the European debate, informed in particular by lessons from US experiences. With reference to the current literature on the subject, the author argues that it is possible to draw insights from international best practice - such as the clusters present in the Boston area and the 'innovation districts' that have been growing across the US over the past few years - and assumes that some similarities exist between 'innovation clusters' and 'smart specialisation'. Following the in-depth discussion of the main disciplinary schools of thought about the key features of the RIS3 and the ways in which it resembles and diverges from cluster policy, the paper proposes a critical interpretation of what may be deemed an 'innovation strategy' at the urban level. Lessons drawn from the Boston innovation strategy may be considered significant with respect to the RIS3 path to be implemented in European Union regions and urban areas. The paper concludes that, in order to pursue a genuinely place-based and entrepreneurial innovation process, it is necessary to support grassroots projects - both business and social - rather than to prioritize only top-down, economic and 'real-estate' driven planning initiatives.
Keywords: EU-Programm; Regionalplanung; Standortplanung; Stadtteilplanung; Wirtschaftsförderung; Innovationsförderung